PENGARUH JENIS DAN KONSENTRASI ZPT ALAMI TERHADAP PERTUMBUHAN STEK LADA (Piper nigrum L.) - Nana Ariska; Sumeinika Fitri Lizmah; Fajri Fajri (Universitas Teuku Umar, 2020)
Pepper (Piper nigrum L.) is a high economic value estate crop. Cuttings play animportant role in seedling pepper plants because it is more effective, an effort to overcome the failure in root growth in cuttings is to provide growth regulators. In its use, the effectiveness of ZPT is influenced by the type and concentration of ZPT used. This study aims to determine the effect of the type and concentration of natural PGR on the propagation of pepper by cuttings and the interaction of the two factors. This research was conducted in the experimental garden of theFaculty of Agriculture, Teuku Umar Meulaboh University from January to March 2020. The material used was cuttings of pepper plants obtained from pepper growers, shallots, bamboo shoots, banana weevil, alluvial soil, manure, polybags, hooded plastic and raffia. The tools used are: hoes, scissors, knives, gauges, fansticks, cameras, stationery and cameras. The design used in this study was a 3 x 6 factorial randomized block design (RBD) with three replications. Natural ZPT type factor (J) consists of three levels, namely: J1 = Shallot Extract, J2 = Bamboo Shoot Extract, J3 = Banana Weevil Extract. Variables observed were percentage of growth, number of shoots, number of leaves, root length, root wet weight and root dry weight. F test results on the analysis of variance showed that the type of natural PGR had a very significanteffect on root length. Significantly affect the growth potential, the number of shoots 45, 60 and 75 HST, the number of leaves 45, 60 and 75 HST, root wet weight and root dry weight. But no significant effect on the number of buds 30 HST and leaf number 30 HST. Keywords: Pepper cuttings, Type of ZPT, Concentration.